Mobility infrastructures as public spaces. A reconnection project - Giovannoni, Giulio (TeMA - Journal of Land Use, Mobility and Environment, 2022)
The essay deals with the theme of reconnecting, through urban planning and public works design, the relationship between mobility infrastructure and spaces for social life. The first part contains a historical reflection on the integration between mobility infrastructures, commercial/directional facilities and public spaces. The second section analyzes the consequences determined by the advent of the car and the urban explosion on this relationship. The third part of the essay develops a critical reflection on the way we look at the relationship mobility/public space and proposes a change of perspective. The concluding section of the essay contains some specific proposals, of a planning and normative kind, to recover the integration between mobility facilities and public/private spaces for social life in contemporary cities.